The Granny - O'Carroll, Brendan (Dublin The O'Brien Press Ltd, 2012)
The final book in the Agnes Browne trilogy. At forty-seven years of age Agnes, now thirteen years happily widowed, enters the 1980s with a fruit stall in Moore Street, a French lover and six children, five of them in their twenties. Becoming a grandmother is a terrible shock to her system, especially as Agnes suffers every one of her daughter-in-law's labour pains! And as the family expands so do the problems - one son's inevitable brush with the law, the heartbreak of emigration. But Agnes Browne is nothing if not a fighter, and she squares her shoulders, offers up a quick one to her departed.
Keywords: Women -- Ireland -- Ireland--Dublin